Prática de ensino supervisionada : desenho A, 10º e 12º anos : metodologia projectual no-do design - Saraiva, Cláudia Isabel Gregório Ramos (2014)
The report presented, was prepared under the Master in Teaching Visual Arts in the 3rd Cycle of Basic Education and Secondary Education, refers to the practice of supervised teaching, held during the academic year 2011/12, at High School Campos Melo (Portugal, Covilhã), at two middle school classes of the scientific-humanistic course of Visual Arts. The theoretical and practical research, was under the theme of Projectual Methodology in-at Design and its integration in visual arts education. This report is structured in three parts: theoretical and practical research/study, curriculum analysis, and supervised teaching practice. The first part, dedicated to the study of Projectual Methodology in-at Design, has been divided in two chapters. The first aims to understand the concepts attached to design and to the projectual methodology, by contextualize, understand and defining this concepts. The second chapter focuses in the historical evolution of Projectual Methodologies, presenting some authors and their proposals, in order to understand what can be read in common. The second part focuses on the analyses of the disciplines directly related to design project, held at the disciplinary teaching group (grupo 600), in order to reflect the importance of the project teaching concept. Also some projects are presented, that promote project-oriented attitude and show concerns, in a broader context outside de world of school. As a reflection, is presented a practical exercise, a proposal to outline a discipline with a different approach. The third and last part, structured in two chapters, corresponds to the entire work done carried out under the supervised teaching practice. In the first chapter, the High School Field Melo, the Scientific and Humanistic Course of Visual Arts, the core stage and the classes where the pedagogical practice underwent is contextualized and characterized. The final chapter, focuses on the pedagogical practice and describes, analyzes and reflects the activities throughout the school year.